2009
DOI: 10.1302/0301-620x.91b3.20820
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of deep-vein thrombosis in fractures below the knee

Abstract: The incidence of deep-vein thrombosis and the need for thromboprophylaxis following isolated trauma below the knee is uncertain. We have investigated this with a prospective randomised double-blind controlled trial using low molecular weight heparin with saline injection as placebo in patients aged between 18 and 75 years who had sustained an isolated fracture below the knee which required operative fixation. All patients had surgery within 48 hours of injury and were randomised to receive either the placebo o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 43 publications
2
80
1
1
Order By: Relevance
“…We found increasing age to be a risk factor for the presence of a DVT, as have others [9,10,[12][13][14] . Although we collected data on other potential risk factors, none of these attained statistical significance in multiple logistic regression.…”
Section: Discussionsupporting
confidence: 86%
“…We found increasing age to be a risk factor for the presence of a DVT, as have others [9,10,[12][13][14] . Although we collected data on other potential risk factors, none of these attained statistical significance in multiple logistic regression.…”
Section: Discussionsupporting
confidence: 86%
“…A prospective randomized controlled trial by Goel et al showed no significant difference in the incidence of DVT with chemical prophylaxis or placebo in fractures below the knee, although tibia plateau fractures showed a trend towards increased risk of VTE. 9 Unfortunately their study was prematurely closed due to lack of funding. The incidence of VTE after tibia fracture is believed to be low.…”
Section: Discussionmentioning
confidence: 99%
“…patient population (with 20 associated references [153][154][155][158][159][160][164][165][166]174,176,177,179,181,183,186,189,[192][193][194] ), 17 trials in knee surgery patient population (with 18 associated references 152,156,157,[161][162][163][167][168][169][171][172][173]175,178,180,182,187,196 ), seven trials in medical patient population (with seven associated references 170,184,185,188,190,191,197 ) and one trial (with one associated reference 195 ) involving both hip and knee surgery patients. Thirty-nine of the trials were multicentre and four were single-centre trials.…”
Section: Figure 32mentioning
confidence: 99%